“INSIDER TRADING“DALAM KEGIATAN PASAR MODAL MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1995 - PUTRA, I.B PRIYANTA; DARMAWAN, NI KETUT SUPASTI; WESTRA, I KETUT (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
Capital Marketis astock tradingactivityundertakenby a companyandsociety,capital marketis seen asone of theeffective means toaccelerate the developmentof aState, the Capital Marketgivesan advantage toevery strata of societyand the State.Capitaltransparencyprincipleisthe coreissueofcapital markets. However,therearemanyviolations of theprinciple of transparencyinthecapital marketpractice, thereare threetypes ofviolationsin thecapital market, thethree offenses, namely: InsiderTrading, Market Manipulation
Keywords: Transparency. Insider Trading, Development, Capital Market